Effect of Cotton Seed Cake on Cattle Milk Yield and Composition at Livestock Research and Development Station Surezai, Peshawar, Pakistan - Uddin, Hayaz; Rahman, Abdur; Khan, Rajwali; khan, Bakht Daraz; Muhammad, Din; Farid, Kamran; Anwar, Khurshaid; Ullah, Sibghat; Ali, Zubair (Pakistan Journal of Nutrition, 2013)
The present study was conducted at Livestock Research and Development Station Surezai, Peshawar during June to August 2011. The objectives of this study were to determine the effect of Cotton Seed Cake (CSC) on milk yield, milk composition, feed intake, Body Condition Score (BCS) and live weight of Holstein Friesian (HF) crossbred cows. A total of nine mid-lactation crossbred cows were randomly distributed to three groups and allocated to diets containing zero (control), 20 and 35 percent CSC. All the three rations were Isocaloric and Isonitrogeniuos. Each cow was given a daily feed ration according to NRC standards. Mean daily milk yield differed (P<0.05) among all treatment groups. However, highest milk yield 5.68±0.096 kg/day was recorded for cows feed 35% CSC while the control group (0% CSC) produced the least yield 4.473±0.184 kg/day. Cows on 35% CSC produced higher milk fat 4.46±0.22 percent and have significant (P<0.05) effect on milk fat content while the control group produced the least 3.35±0.22 percent fat. CSC had no significant (P>0.05) effect on protein content in milk as cows on 35% CSC diet produced the least 2.7±0.09 percent protein, while the control group produce the highest 3.00±0.09 percent. The concentration of Lactose and total milk solid not fat (SNF) content was higher (P>0.05) for control group than the cows fed on other diet. There was significant (P<0.05) difference in daily feed intake as the cows on 35% CSC diet had the highest daily feed intake of 32.478±0.31kg/day while the control group had the least intake 29.138±0.31kg/day. Experimental rations had no significant (P>0.05) effect on mean changes in BCS. The Live weight was not effected significantly (P>0.05) by rations, However highest mean change in weight gain of 7.66±4.95kg/45day was recorded for cows fed ration having 35% CSC while least 5.00 ±7.90 kg/45day was recorded for cows fed zero% CSC in the ration. Economically ration having 35% CSC had the lowest cost of milk production (Rs: 17.14/kg) as compared to ration having 20% (Rs.19.68/kg) and Zero% CSC (Rs.21.6/kg). These results concluded that milk yield; milk fat and feed intake was increased with supplementation of high level of cotton seed cake in the dairy cattle ration. Higher proportion of CSC (35%) has shown the best efficiency of production as compare to other rations.